Peculiarities of Interventions in Chronic Coronary Occlusions in Patients with CHD after CABG. State of the Art and Actual Experience - Furkalo, S. N. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Within 10 years after coronary artery bypass grafting (CABG) only 60 % of vein grafts and 90 % of internal mammary artery (IMA) grafts remain patent. Chronic total occlusions (CTO) in patients after CABG suggest more ad-vanced state of atherosclerosis. Although precise mechanism of atherosclerosis in these patients is unknown, several clinical studies reported that atherosclerosis progression occurs more rapidly in grafted than in non-grafted arteries. These data support the fact that IMA has favorable metabolic effect not only in the bypass, but also in the bypassed artery, which, according to the authors, is defined by NO products. The frequency of occlusion of initially stenotic arteries in the proximal or distal segment was about 22 % after the application of IMA grafts and on average 48 % after autovenous grafts. According to literature data, in multivariate analysis, bypass interventions are independently associated with higher hospital mortality and perioperative complications. Mortality rate was 2.6 % if the artery recanalization was successful, 5.2% in case of a partial success and 8.2 % in case of failure. This paper presents the analysis of possible interventional approaches to recanalization of the coronary bed in patients after CABG, discusses actual experience and practical developments. Fifty-two patients underwent recanalization of chron-ic occlusions of the coronary arteries at different times after CABG with a total technical efficiency of 75 %. In 11 patients with СTO, repeated recanalization attempts were made with an efficiency of 54.5 %. The third attempt was effective in two patients. Thus, the secondary efficacy of interventions was about 88 %. An intravascular ultrasound (IVUS) was used in 3.8 % of patients. One patient died during intervention as a result of collateral rupture at an attempt to perform retrograde approach when a “dry tamponade” occurred that led to cardiogenic shock. Thus, CTO after CABG have unfavorable characteristics for recanalization and are more technically demanding than occlusion of arteries without prior coronary artery bypass grafting. Retrograde access is much more common here, and the effectiveness of intervention is significantly lower than that in primary patients. Repeated attempts to recapitalize the artery in case of prior unsuccessful attempt may significantly improve the results and were effective in half of the cases.